Differential analysis of ergosterol function in response to high salt and sugar stress in Zygosaccharomyces rouxii. Issue 1 (6th August 2022) - Song, Na; Xia, Huili; Yang, Qiao; Zhang, Xiaoling; Yao, Lan; Yang, Shihui; Chen, Xiong; Dai, Jun
Abstract: Zygosaccharomyces rouxii is an osmotolerant and halotolerant yeast that can participate in fermentation. To understand the mechanisms of salt and sugar tolerance, the transcription levels of Z. rouxii M 2013310 under 180 g/L NaCl stress and 600 g/L glucose stress were measured. The transcriptome analysis showed that 2227 differentially expressed genes (DEGs) were identified under 180 g/L NaCl stress, 1530 DEGs were identified under 600 g/L glucose stress, and 1278 DEGs were identified under both stress conditions. Then, KEGG enrichment analyses of these genes indicated that 53.3% of the upregulated genes were involved in the ergosterol synthesis pathway. Subsequently, quantitative PCR was used to verify the results, which showed that the genes of the ergosterol synthesis pathway were significantly upregulated under 180 g/L NaCl stress. Finally, further quantitative testing of ergosterol and spotting assays revealed that Z. rouxii M 2013310 increased the amount of ergosterol in response to high salt stress. These results highlighted the functional differences in ergosterol under sugar stress and salt stress, which contributes to our understanding of the tolerance mechanisms of salt and sugar in Z. rouxii . Abstract : Ergosterol synthesis has functional differences in Zygosaccharomyces rouxii response to high salt and high sugar stress.